2012
DOI: 10.1186/1471-2407-12-368
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus exerts potent oncolytic effects in head and neck cancer cell lines that are independent of signalling in the EGFR pathway

Abstract: BackgroundReovirus exploits aberrant signalling downstream of Ras to mediate tumor-specific oncolysis. Since ~90% squamous cell carcinomas of the head and neck (SCCHN) over-express EGFR and SCCHN cell lines are sensitive to oncolytic reovirus, we conducted a detailed analysis of the effects of reovirus in 15 head and neck cancer cell lines. Both pre- and post-entry events were studied in an attempt to define biomarkers predictive of sensitivity/resistance to reovirus. In particular, we analysed the role of EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…30, 36, 37, 38 A Reolysin-based combination with platinum- and taxane-based therapy has proven to be especially effective and has advanced into a phase III clinical trial in patients with head and neck cancer. 11, 39, 40, 41 Although these standard agents have multifaceted mechanisms of action that contribute to their anticancer activity, both have been shown to stimulate ER stress. 16, 42, 43 Our data in pancreatic cancer models suggest that platinum- and taxane-triggered ER stress may significantly contribute to the efficacy of this combination.…”
Section: Discussionmentioning
confidence: 99%
“…30, 36, 37, 38 A Reolysin-based combination with platinum- and taxane-based therapy has proven to be especially effective and has advanced into a phase III clinical trial in patients with head and neck cancer. 11, 39, 40, 41 Although these standard agents have multifaceted mechanisms of action that contribute to their anticancer activity, both have been shown to stimulate ER stress. 16, 42, 43 Our data in pancreatic cancer models suggest that platinum- and taxane-triggered ER stress may significantly contribute to the efficacy of this combination.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of caspase 3 has also been reported to be necessary for development of reovirus induced encephalitis [9]. On the contrary, a recent study reported that reovirus exerts potent apoptotic effects in head and neck cancer cell lines in a caspase 3 independent manner [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Activating mutations in KRAS occur in approximately 40-45% of patients with CRC [10]. Recent clinical data demonstrates that the anti-EGFR antibodies, cetuximab and panitumumab, are ineffective in patients with CRC whose tumors harbor KRAS mutations [12].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of the PKR (dsRNA-activated protein kinase) has been identified to be one of the major factors that inhibited the translation of viral genes and viral replication in untransformed cells [11], [12]. While Ras activation has been proven to enhance reolysis, further research has shown that reovirus can exert its oncolytic effects independent of this pathway [13]. This highlights the complexity of the mechanism in which reovirus works in cancer cells and that our current understanding is insufficient to pinpoint a definitive biomarker of susceptibility to reovirus.…”
Section: Introductionmentioning
confidence: 99%